The Role of Appreciation of Ethics and Civilization in Fostering Social Cohesion among Malaysian Higher Education Students (Contrarius Series: Law & Social Justice, 2026)
Malaysia’s higher education institutions face both challenges and opportunities arising from cultural diversity. The Appreciation of Ethics and Civilization, a compulsory university course, was introduced to promote tolerance and a shared national identity; however, its impact on social cohesion is often limited by weak integration with students’ everyday experiences. This study examines the role of the Appreciation of Ethics and Civilization course in fostering social cohesion among Malaysian university students. Using a qualitative approach, the study analyses primary data comprising course syllabus, students’ assignments, and course feedback. The role of Appreciation of Ethics and Civilization is examined through three interrelated dimensions: knowledge acquisition of ethics and civilization, interracial bonding through learning activities, and student acceptance of the course. Findings show that these dimensions mutually reinforce one another, enhancing students’ appreciation of cultural diversity and national unity. The study highlights Appreciation of Ethics and Civilisation's potential as a catalyst for social cohesion, offering practical implications for promoting harmony in Malaysia’s plural society. The study also demonstrates to worldwide communities how ethics education when aligned with relational and experiential learning can promote social cohesion in multicultural societies.